2020
DOI: 10.3389/fpls.2020.595792
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Heat-Induced Plastidial Stress Granules Reveal New Insight Into Arabidopsis Stress Response

Abstract: Plants exhibit different physiological and molecular responses to adverse changes in their environment. One such molecular response is the sequestration of proteins, RNAs, and metabolites into cytoplasmic bodies called stress granules (cSGs). Here we report that, in addition to cSGs, heat stress also induces the formation of SG-like foci (cGs) in the chloroplasts of the model plant Arabidopsis thaliana . Similarly to the cSGs, (i) cpSG assemble rapidly in response to stress and disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…Previously, heat stress was found to induce relocalization of splicing factors with disordered domains, for example, serine/arginine-rich protein SR45, into enlarged nuclear speckles (Ali, Golovkin, & Reddy, 2003;Reddy, Day, Göhring, & Barta, 2012), which could underlie alternative splicing of pre-mRNAs. The PrLDs of mRNA-binding proteins might be critical to trigger thermosensitive condensation into stress granules (Chodasiewicz et al, 2020;Emenecker, Holehouse, & Strader, 2020;Kosmacz et al, 2019 (Chakrabortee et al, 2016). Investigating the effect of temperature on the coalescence of these factors in vitro could yield interesting results.…”
Section: Heat Sensing Is Mediated By Lipid Signalsmentioning
confidence: 99%
“…Previously, heat stress was found to induce relocalization of splicing factors with disordered domains, for example, serine/arginine-rich protein SR45, into enlarged nuclear speckles (Ali, Golovkin, & Reddy, 2003;Reddy, Day, Göhring, & Barta, 2012), which could underlie alternative splicing of pre-mRNAs. The PrLDs of mRNA-binding proteins might be critical to trigger thermosensitive condensation into stress granules (Chodasiewicz et al, 2020;Emenecker, Holehouse, & Strader, 2020;Kosmacz et al, 2019 (Chakrabortee et al, 2016). Investigating the effect of temperature on the coalescence of these factors in vitro could yield interesting results.…”
Section: Heat Sensing Is Mediated By Lipid Signalsmentioning
confidence: 99%
“…RNA-binding proteins are known to form heat-triggered aggregates resembling HSGs [ 41 ]. Importantly, CP29A is detected in recently-identified heat-induced chloroplast stress granules, where it is suggested to function as a scaffold protein for their assembly [ 49 ]. Given its presumable inactive state, CP31A, and perhaps, CP29B may form similar stress-dependent granules or protein aggregate centers (PACs), which could be facilitated by chaperones including HSP70 family proteins as observed in yeast [ 41 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 2', 3'-cAMP, and 2', Corroborating the published work, seven of the 31 high-confidence 2', 3'-cGMP targets predicted by SLIMP (prediction probability for interaction > 80 %) are characterized by RRM domain, Rbp47 among them, which is 12.8-times more than expected by chance. The list also contains a plastidial protein CP29, speculated to play a similar role to the Rbp47 for the assembly of plastidial SGs (Chodasiewicz 2020). Furthermore, of the 31 proteins, six were shown to sequester in either cytosolic or plastidial SGs (Chodasiewicz 2020, M. G. Kosmacz 2019.…”
Section: Novel Targets Of 2' 3' Cyclic Nucleotides and Dipeptides Identified By Slimpmentioning
confidence: 99%
“…The list also contains a plastidial protein CP29, speculated to play a similar role to the Rbp47 for the assembly of plastidial SGs (Chodasiewicz 2020). Furthermore, of the 31 proteins, six were shown to sequester in either cytosolic or plastidial SGs (Chodasiewicz 2020, M. G. Kosmacz 2019. Based on the SLIMP results, we now hypothesize that 2', 3'-cNMP facilitate both cytosolic and plastidial SGs formation via binding to the RRM motif of the SGs proteins.…”
Section: Novel Targets Of 2' 3' Cyclic Nucleotides and Dipeptides Identified By Slimpmentioning
confidence: 99%